Incidence, prevalence, and real-world treatment patterns in chronic myeloid leukemia: results from a population-representative German claims data analysis - Saußele, Susanne; Kohlbrenner, Katharina; Vogelmann, Tobias; Schubert, Tino (Oncology research and treatment, 2022)
Introduction: Real-world data on usage of 1st-, 2nd-, and 3rd-generation tyrosine kinase inhibitor (TKI) in chronic myeloid leukemia (CML) are scarce. This study therefore aimed to analyze the use of different TKIs used in 1st- and 2nd-line treatment and the frequency of TKI switches in CML. Methods: This observational study was based on the InGef research database, an anonymized representative claims dataset in Germany (n = 4 million). An incidence and prevalence patient CML cohort was followed for 5 and 3 years. Analyses regarding incidence, prevalence, and therapy distribution were performed descriptively. Results: 151 patients were included in the incidence and 636 patients in the prevalence cohort. This resulted in an incidence of 1.8 (95% confidence interval [CI]: 1.34-2.20) and a prevalence of 14.9 (95% CI: 13.70-16.03) per 100,000 inhabitants. For the incidence cohort, data on 1st-line therapy were available for 124 patients and distributed across imatinib (N = 52), nilotinib (N = 44), dasatinib (N = 12), chemotherapies as hydroxycarbamide (N = 11), and ponatinib/bosutinib (N = 5). Twenty-six percent of patients switched TKI therapy at least once in 3 years. In the prevalence cohort, 423 patients (66.5%) had claims on existing or newly emerged cardiovascular diseases (CDs). No significant differences (p = 0.32) between TKIs in patients with CD were found. Discussion: Every fourth patient switched TKI therapy within the first 3 years after treatment initiation. Switches were more likely when hints of disease progression or intolerability were observable in the database.